The Use Of The Indonesian Language In International Contracts After The Circular Letter Of The Supreme Court Number 3 Of 2023 As Guidelines For The Implementation Of Duties For Courts - Yustina Anggraeni; Moh. Saleh Moh. Saleh (Eduvest - Journal of Universal Studies, 2024)
The use of the Indonesian language in memoranda of understanding and agreements with foreign parties is mandated as regulated in Law Number 24 of 2009 concerning the Flag, Language, State Institutions, and National Anthem as well as Presidential Regulation Number 63 of 2019 concerning the Use of the Indonesian Language. However, the provisions do not clearly stipulate the legal consequences if not adhered to, leading to the issuance of Supreme Court Circular Letter Number 3 of 2023 regarding the Implementation of Formulations from the Plenary Meeting of the Supreme Court Chamber in 2023 as Guidelines for the Implementation of Duties for Courts. This raises questions about the status of the Supreme Court Circular Letter within the National Legal System and the legal implications of the Supreme Court Circular Letter regarding the use of the Indonesian language in memoranda of understanding and agreements between foreign parties.